Attitudes of employers towards people with visual impairment: a scoping review - Castle, Claire L. (Frontiers in Rehabilitation Sciences, 2024)
This scoping review explored literature relating to employer attitudes towards employees and candidates with visual impairment (VI). Systematic searches identified 17 relevant articles published since 2018. Thematic synthesis highlighted findings relating to several themes: explicit and implicit attitudes of employers; employer concerns, including those relating to employee performance, and the experiences of both customers and colleagues; and factors which might impact on employer attitudes, such as gender and prior experience of having hired someone with VI. Findings indicate a tendency for employers to possess negative or, at best, neutral attitudes towards people with VI, and the central role that improved knowledge of VI and the capabilities of people with VI may play in generating positive employer attitudes. The review highlights the need for further exploration of this topic, particularly given the limited geographical spread of recent research, and a lack of consideration of the shared experience of employer and employee.